1995
DOI: 10.1021/bi00037a016
|View full text |Cite
|
Sign up to set email alerts
|

The Hexopyranosyl Residue That Is C-Glycosidically Linked to the Side Chain of Tryptophan-7 in Human RNase Us Is .alpha.-Mannopyranose

Abstract: Recently, the novel C-glycosidic linkage of a hexopyranosyl residue to the indole ring of tryptophan residue 7 of human RNase U(s) was reported [Hofsteenge, J., Müller, D. R., de Beer, T., Löffler A., Richter, W. J., & Vliegenthart, J. F. G. (1994) Biochemistry 33, 13524-13530]. Identification of this monosaccharide is a prerequisite for studies of its biosynthesis and its biological relevance. Using vicinal proton-proton coupling constants and rotating-frame nuclear Overhauser enhancements, ewe demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
87
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 31 publications
10
87
0
1
Order By: Relevance
“…An additional anomeric track is located at 5.23 ppm. The cross-peak patterns on this anomeric track in 1 H NOE and 1 H TOCSY spectra of denatured RNase 2, as well as the locations of these cross-peaks, are similar to those of the Man H1′ tracks in 1 H ROE 5 and 1 H TOCSY spectra of C-linked Man in FT-(C 2 -Man-)WAQW [ Figure 3 and Hofsteenge et al (1994) and de Beer et al (1995)]. This includes the typical, intense NOE/ROE 5 cross-peak that indicates that Man H1′ and Man H6′ are close in space (Figure 3).…”
Section: Stability Of the O-mannosylated Syntheticmentioning
confidence: 65%
See 1 more Smart Citation
“…An additional anomeric track is located at 5.23 ppm. The cross-peak patterns on this anomeric track in 1 H NOE and 1 H TOCSY spectra of denatured RNase 2, as well as the locations of these cross-peaks, are similar to those of the Man H1′ tracks in 1 H ROE 5 and 1 H TOCSY spectra of C-linked Man in FT-(C 2 -Man-)WAQW [ Figure 3 and Hofsteenge et al (1994) and de Beer et al (1995)]. This includes the typical, intense NOE/ROE 5 cross-peak that indicates that Man H1′ and Man H6′ are close in space (Figure 3).…”
Section: Stability Of the O-mannosylated Syntheticmentioning
confidence: 65%
“…Recently, it was found that Trp-7 in human RNase 2 1 is modified by C-glycosidic attachment of an R-mannosyl residue (Hofsteenge et al, 1994;de Beer et al, 1995). In contrast to the previously known N-and O-glycosidic linkages to asparagine and serine, or threonine, the mannopyranosyl C1′ atom is in this case directly linked to the C2 atom of the tryptophan indole ring.…”
mentioning
confidence: 88%
“…The EGF domains appear to be more compact and less flexible in C8 than in EGF, as judged by a greater similarity between C8␣ and C8␤ EGF domains (root mean square displacement of 1.7 Å, based on C␣ atoms of 30 residues) than between two copies of EGF proteins in the unit cell in their crystal structure (root mean square displacement of 3.3 Å; based on C␣ atoms of 24 residues) (36 Post-translational Modifications-An infrequent modification of proteins is the covalent attachment of a mannopyranosyl moiety to C␦1 of tryptophan via a C-C bond. NMR studies of a peptide derived from mannosylated human RNase indicated that an ␣-mannopyranose is attached (37). However, thus far there is no reported crystal structure of a peptide or protein containing a mannosyl tryptophan.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a ncw type of glycosylatinn, namclx, C-mannosylation, has bccn obserxcd in human RNase 2 (formerly RNasc ['s) [1,21. The anomeric carbon atom of an a-DmannolLvranosc residue is dircctlv linked to the C2 atom of "l'rp7 {Figurc 1).…”
Section: C-glycosylationmentioning
confidence: 99%